Determinants of contractor satisfaction - Masrom, M. A .N.; Skitmore, Martin; Bridge, Adrian (Routledge Taylor & Francis Group, 2013)
Performance in the construction industry is increasingly scrutinized as a result of the delays, cost overruns and poor quality of the industry’s products and services. Increasingly, disputes, conflicts and mismatches of objectives among participants are contributory factors. Performance measurement approaches have been developed to overcome these problems. However, these approaches focus primarily on objective measures to the exclusion of subjective measures, particularly those concerning contractor satisfaction (Co-S). The contractor satisfaction model (CoSMo) developed here is intended to rectify the situation. Data derived from a questionnaire survey of 75 large contractors in Malaysia in respect of a key project are analysed to identify participant factors and their strength of relationship with Co-S dimensions. The results are presented in the form of eight regression equations. The outcome is a tool for use by project participants to provide a better understanding of how they, and the project, affect contractor satisfaction. The developed model sheds some light on a hitherto unknown aspect of construction management in providing an increased awareness of the importance of major Malaysian construction contractors’ needs in the execution of successful projects.